AMBIENTE LABORAL DE LOS SERVIDORES Y TRABAJADORES DE LA DIRECCIÓN DISTRITAL DE LOS RÍOS DEL MTOP - LARENAS SOJOS, SOLANGE NOEMI (2018)
he Los Ríos District Office of the Ministry of Transport and Public Works, or MTOP, is located on Enrique Ponce Luque Avenue diagonally to the Ecomundo School in the city of Babahoyo, this institution is responsible for the construction and maintenance of the National Road Network In Ecuador, the MTOP Los Ríos car park consists of six dump trucks, a low bed, two asphalt tanks, a backhoe, a mini digger, seven trucks and two road patrols.